2014
DOI: 10.2528/pierm14040311
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Simulation Approach of Aircraft Dynamic RCS

Abstract: Abstract-The Radar Cross Section (RCS) of moving targets varies dramatically with aspect or time. The accuracy of simulated dynamic RCS is very important for radar system simulation. A novel approach to simulate the dynamic RCS of aircraft is proposed in this paper. Firstly, the electromagnetic (EM) model of aircraft is built and the all-space monostatic RCS database calculated. Secondly, the aspect angles (azimuth and elevation) in target coordinate system are calculated from flight path by coordinate transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 10 publications
(10 reference statements)
0
19
0
1
Order By: Relevance
“…Dietary curcumin (0.5% in diet) also improved increased levels of fasting blood glucose in STZ-induced diabetic rats [25,27]. The work of curcumin revealed that an IC 50 value that was 36.9 mmol/L when compared with aldehyde dehydrogenase 1 inhibitors, which are chiefly therapeutic drugs for diabetes.…”
Section: Figmentioning
confidence: 96%
“…Dietary curcumin (0.5% in diet) also improved increased levels of fasting blood glucose in STZ-induced diabetic rats [25,27]. The work of curcumin revealed that an IC 50 value that was 36.9 mmol/L when compared with aldehyde dehydrogenase 1 inhibitors, which are chiefly therapeutic drugs for diabetes.…”
Section: Figmentioning
confidence: 96%
“…The bandwidth of waveform, BFM is 200 MHz, the number of range bins, NFFT is 256, the number of chirps per one burst, Nchirp is 119, and the duration of one chirp, T is 33 µsec. One of the advantages of FMCW radar is its inherent capability of computing the distance as well as the speed of moving object by applying 2‐dimensional fast Fourier transform (FFT) of the FMCW beat frequency . However, in processing FFT, main lobe that obtains the received target signal is not significantly distinguished with side lobe, and thus we reduce the side lobe and amplify the main lobe by applying Hanning window .…”
Section: Experimental Results With Real Fmcw Radarmentioning
confidence: 99%
“…Pasqui et al [10] proposed a method to assess the efficiency of smart-walkers by measuring the time cost of different walkers when users were required to complete a series of movements. Other types of robotics to assist walking and lower limb rehabilitation have also been studied these include a new design of an exoskeleton system presented by Castro et al [11], a new robot design for children with cerebral palsy presented by Giergiel et al [12] and a mechanism model of a lower limb passive rehabilitation system built by Zhang et al [13]. In addition, some researchers have also studied the psychological aspects of lower limb rehabilitation.…”
Section: A Literature Reviewmentioning
confidence: 99%